Conodontos del Ordovícico Superior (Ashgill) en la Serra do Buçaco, Portugal - Moral, Begoña del; Piçarra, José Manuel; Sarmiento, Graciela N. (Coloquios de Paleontología, 2001)
The first Ordovician conodonts from Portugal are described. They were obtained from the Poiares Member of the Ferradosa Formation cropping out in the Buçaco syncline (Central Iberian Zone). Most of the conodont taxa have been identified in open nomenclature due to their preservation conditions. Taphonomic aspects of the conodonts suggest low grade metamorphic conditions (epizone) for their host rocks. This conodont association is composed of taxa characteristic of the Ashgillian Amorphognathus ordovicicus Biozone from the Mediterranean Province of the North Atlantic Domain
Keywords: Portuguese Central Iberian Zone; Buçaco Syncline; Ferradosa Formation; Upper Ordovician; conodonts; Amorphognathus